PENGEMBANGAN MODEL PENGENDALIAN KUALITAS PRODUKSI PIPA PVC MENGGUNAKAN SIX SIGMA, SEVEN TOOLS, DAN STATISTICAL PROCESS CONTROL (SPC) MENUJU ZERO DEFECT MANUFACTURING - Arief andika Putra; Dimas Akmarul Putera; Nellya Wahyuning Sri Gunarti; Muhammad Yusuf Hidayat; Rinci Kembang Hapsari (SIGMA TEKNIKA, 2026)
The purpose of this study is to improve the quality control of PVC pipe products at PT.XYZ by using Six Sigma , Seven Tools, and Statistical Process Control (SPC) methods to achieve zero defect manufacturing. This study applied a quantitative method with the DMAIC approach. The results showed a total production of 89,315.81 kg with defects of 1,521.30 kg, a DPMO value of 3,406.56, and a sigma level of 4.2 sigma. Pareto analysis identified machine M.13 as the main contributor to defects, while the Fishbone diagram revealed that defects were caused by human, machine, material, method, and environmental factors. Improvements were carried out using the 5W+1H method, and P-Chart analysis showed that the production process was still within statistical control limits. The results indicate that the implementation of Six Sigma , SPC, and Seven Tools can improve product quality toward zero defect manufacturing